Understanding Social Aspects on Desalination for Community Adaptation and Resilience in Baja California, México - Mariana Villada-Canela (Social Sciences, 2025)
This article examines the social aspects of seawater desalination, especially as a strategy for community adaptation and resilience to water scarcity in arid and coastal regions, focusing on Baja California, México. This study aims to understand how social, cultural, political-institutional and territorial factors influence the acceptance and implementation of desalination technology. Through an inductive analysis based on a grounded theory methodology, this research employed a literature review and stakeholder semi-structured interviews to identify the potential impacts and key factors affecting desalination projects. Two research questions guided the investigation: (1) What sociopolitical factors influence the implementation of desalination projects in coastal communities? (2) How do these factors shape community responses to desalination initiatives? Through a case study of San Quintin, Baja California, it was found that stakeholder perspectives varied significantly regarding water management strategies. This analysis revealed that successful desalination implementation depends on four key factors: local governance structures, power relations among stakeholders, community engagement processes, and territorial characteristics. These findings suggest that effective desalination projects require integrating technical solutions with robust social processes that include meaningful community participation and the consideration of local contexts. This study contributes to the water adaptation and resilience literature and provides practical insights for policymakers and project developers working on desalination initiatives in similar coastal regions.